ANTIHIPERGLICEMIC THERAPY COMPLIANCE WITH HbA1C LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS AMONG PEKANBARU PROLANIS PARTICIPANTS - Dimas Pramita Nugraha; Eni Karmila Asni; Ligat Pribadi Sembiring Pribadi Sembiring (Buletin Farmatera, 2020)
One of the pillars in the management of Type 2 Diabetes Mellitus (DM) is pharmacotherapy, i.e. the use of antihyperglycemic drugs. Success in DM management is influenced by patient compliance to the pharmacotherapy given. One indicator of controlling Type 2 DM is HbA1c levels. This study aimed to analyze the relationship between antihyperglycemic therapy compliance and the HbA1c levels in Type 2 DM patients in the Chronic Disease Management Program in Pekanbaru. Method. This was a cross-sectional study. Samples were taken by consecutive sampling method. Laboratory examination was carried out to obtain HbA1c levels, the value of which was categorized controlled if <7%. The compliance with the use of antihyperglycemic drugs was assessed using Medication Possession Ratio (MPR). Patients were considered compliant if they had an MPR of ≥80%. Data were analyzed using the Fisher Exact test. Results. Most of the 48 patients had uncontrolled HbA1c levels (87,5%). The level of non-compliant patients was also very high (91,7%). This study showed a significant relationship between pharmacotherapy compliance and HbA1c levels (p <0.05). Discussion. There was a relationship between pharmacotherapy compliance and the level of HbA1c in Type 2 DM patients.  Physicians should pay more attention to patients with low compliance as it may increase the risk to a high HbA1c level